Dose related in vitro effects of ranitidine and cimetidine on basal and ACTH-stimulated steroidogenesis. Issue 10 (October 1986) - Kenyon, C J; Fraser, R; Birnie, G G; Connell, J M; Lever, A F
Abstract : Isolated bovine adrenocortical cells were incubated with and without 3 ng/ml ACTH, with various concentrations (10-1000 micrograms/ml) of either cimetidine or ranitidine. Cortisol, corticosterone, and deoxycorticosterone outputs were measured. Cimetidine and ranitidine at 320 and 1000 micrograms/ml inhibited ACTH-stimulated corticosterone and cortisol synthesis and cimetidine decreased basal cortisol synthesis. The inhibitory effects of cimetidine on cortisol synthesis were approximately 10 times greater than those of ranitidine. Cimetidine (1000 micrograms/ml), but not ranitidine increased deoxycorticosterone synthesis by ACTH-stimulated cells, indicating inhibition of 11 beta-hydroxylation in the adrenal steroidogenic pathway. Although doses of cimetidine and ranitidine which produce these in vitro effects are much greater than plasma concentrations in normal clinical use, they might be important in acutely ill patients given intravenous bolus injections of cimetidine, or if either antagonist were accumulated by the adrenal to produce high intracellular concentrations.